WEAKNESSES OF THE NEGATIVE PUBLICATION SYSTEM WITH POSITIVE ELEMENTS IN AGRARIAN LAW IN INDONESIA - Suharyono, Suharyono (Nurani, 2021)
In the negative publication system with positive elements in agrarian law in Indonesia at the implementation level, there are still a number of weaknesses, both weaknesses from the aspect of the norms for the purpose of land registration, aspects of legal responsibility and the system of imposing sanctions. There will be 3 (three) weaknesses in the Negative Publication System (positive elements) which are used as the basis for Land Registration by Government Regulation/PP Number 24 of 1997, namely: first; the norming system because it is imperative (norm imperative) and open (openbaar norm) which provides an opportunity for other parties to prove that they are the real owners of the land, thus resulting in legal disputes that must be resolved through the courts; second; the norm of legal responsibility for BPN/Kakan Land Officials who make mistakes in the implementation of land registration is not regulated in a negative publication system with positive elements, so that BPN/Land Office officials are not legally responsible when a certificate of land rights is canceled or declared invalid by a court decision; and third; norms and system for imposing sanctions for Land Registration Officers (BPN officials) who make mistakes in the implementation of land registration in Government Regulation/PP Number 24 of 1997 is not regulated. Keywords: Negative Publications, Positive Elements, and Agrarian Law.